A Market-Based Approach to Capacity Development : How Uganda's Local Governments are Breaking New Ground - Nelson, Mark (World Bank, Washington, DC, 2012)
For many developing countries, capacity development means donor-sponsored training programs and outside experts. But a noteworthy example in Uganda shows that capacity development may work better and be more sustainable when local market forces are unleashed to provide for local capacity needs. The Uganda case spotlights an approach supported by the World Bank and other partners that has focused on improving the capacities of Uganda's local governments, which since the 1990s have been part of one of Africa's most ambitious decentralization processes. In that program, Uganda's ministry of local government has used World Bank and other donor financing to create a set of incentives aimed at improving the performance of the country's local governments. Part of the approach was not only a system to reward high-performing local governments, but actions aimed at stimulating both supply and demand for capacity development at the local level.